The Sixth Side of the Pentagon - Marker, Chris; Reichenbach, François; Daval, Tony; Odasso, Christian (Planète Chris Marker, 2013)
On October 21, 1967, over 100,000 protestors gathered in Washington, D.C., for the mobilization to end the war in Vietnam. It was the largest protest gathering yet, and it brought together a cross-section of liberals, radicals, hippies and Yippies. For many it was the transition from simply marching against the war, to taking direct action to stop the "American war machine." [Cover]